Immature defense mechanisms predict poor response to psychotherapy in major depressive patients with comorbid cluster B personality disorder - Scaini,Carolina Rheingantz (2022)
Objective: To evaluate the impact of defense mechanisms at baseline on depressive symptoms after brief psychotherapies and after 6-months of follow-up among depressed patients with and without cluster B personality disorders (PDs). Methods: This quasi-experimental study nested within a randomized clinical trial included a clinical sample of adults (18-60 years) diagnosed with major depressive disorder using the Mini-International Neuropsychiatric Interview. The Millon Clinical Multiaxial Inventory-III was applied to assess PD, the Defense Style Questionnaire 40 was used to analyze defense mechanisms, and the Beck Depression Inventory was used to measure the severity of depressive symptoms. Adjusted analysis was performed by linear regression. Results: The final sample consisted of 177 patients diagnosed with major depressive disorder, of whom 39.5% had cluster B PDs. Immature defenses at baseline significantly predicted the persistence of depressive symptoms at post-intervention and at 6-months of follow-up only in patients with PDs. Conclusion: In depressed patients with cluster B PDs, immature defenses predicted a poor response to brief therapies. The assessment of immature defenses at baseline can help identify patients at greater risk of poor therapeutic results and enable more appropriate treatment choices.